A 16-bit 300-kS/s foreground calibration SAR ADC with single-ended/differential configurable input modes. (October 2022) - Bao, Yuanxin; Ye, Le
Abstract: This paper presents a 16-bit 300-kS/s foreground calibration successive approximation register analog-to-digital converter (SAR ADC) with single-ended/differential configurable input modes. A foreground calibration method is implemented to correct mismatch errors in a capacitive digital-to-analog converter (CDAC) and reduce the capacitor size, thereby lowering the current consumption. The total capacitor size is reduced to 10 pF from the 485.6 pF required for 16-bit matching. A self-calibrated low-offset comparator is proposed to avoid the calibration being out of range. An improved merged capacitor switching technique is proposed to realize the configuration of the single-ended/differential input modes. Compared to active single-ended-to-differential converter solutions or single-ended SAR ADCs, the proposed solution achieves a smaller chip area and better power efficiency. A prototype was fabricated in 110-nm CMOS technology. It achieves a signal-to-noise and distortion ratio of 79.8 dB and integral nonlinearity of −1.5/+1.1 LSB with no missing codes. The power consumption of the ADC from a 3-V supply is 1.07 mW.